ANALISIS DIGITAL MARKETING DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU NIKE - Feba Dinova Dex Tovtora S; Abdul Rauf; Dhea Zatira (Universitas Muhammadiyah Tangerang, 2022)
ABSTRACTThe purpose of this study was to determine Digital Marketing and Product Attributes to Purchase Decisions for Nike Shoe Products at Muhammadiyah University Students, Tangerang. This study uses a quantitative approach. The population of this study has a scale of about 1000-5000 people consisting of students and students of the Muhammadiyah University of Tangerang. The sampling method used in this study is the Accidental Sampling method. In this study, the samples to be taken were all students of the Muhammadiyah University of Tangerang, namely 100 students consisting of several classes. Analysis of the data in this study using SPSS version 25. The data testing technique used in this study was multiple linear regression. The results showed that there was a significant influence of Digital Marketing and Product Attributes on Nike Shoe Product Purchase Decisions at Muhammadiyah University Tangerang Students.Keywords: Purchase Decision, Digital Marketing and Product Attributes